2016
DOI: 10.1002/cbdv.201600194
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomicidal Effects of the Essential Oils of Citrus limonia and Citrus reticulata Against Schistosoma mansoni

Abstract: We report the in vitro schistosomicidal effects of the essential oil obtained from Citrus limonia leaves (CL-EO) and C. reticulata fruit peels (CR-EO), cultivated in Brazil, against Schistosoma mansoni worms. Limonene (29.9%), β-pinene (12.0%), sabinene (9.0%), citronellal (9.0%), and citronellol (5.8%) are the major constituents of CL-EO; limonene (26.5%), γ-terpinene (17.2%), linalool (11.1%), octanal (8.0%), myrcene (6.2%), and capraldehyde (3.9%) predominate in CR-EO. CL-EO displayed moderate lethal concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…In this study, DA‐EO displays very promising schistosomicidal activity against Schistosoma mansoni adult worms in vitro , with LC 50 values of 6.50 ± 0.38, 3.66 ± 1.06, and 3.65 ± 0.76 μg/ml at 24, 48, and 72 h, respectively. Moreover, DA‐EO was much more active than other essential oils previously investigated by our research group, which only presented significant activity only at concentrations equal to or higher than 100 μg/ml . Monzote and co‐workers reported that the monoterpene ascaridole accounted for the antileishmanial effect of DA‐EO collected in Cuba, with a LC 50 = 0.1 ± 0.01 μg/ml.…”
Section: Resultsmentioning
confidence: 58%
“…In this study, DA‐EO displays very promising schistosomicidal activity against Schistosoma mansoni adult worms in vitro , with LC 50 values of 6.50 ± 0.38, 3.66 ± 1.06, and 3.65 ± 0.76 μg/ml at 24, 48, and 72 h, respectively. Moreover, DA‐EO was much more active than other essential oils previously investigated by our research group, which only presented significant activity only at concentrations equal to or higher than 100 μg/ml . Monzote and co‐workers reported that the monoterpene ascaridole accounted for the antileishmanial effect of DA‐EO collected in Cuba, with a LC 50 = 0.1 ± 0.01 μg/ml.…”
Section: Resultsmentioning
confidence: 58%
“…Previous reports of EOs from fruit peel from other C. reticulata specimens showed that terpenes limonene, sabinene, linalool, ɣ-terpinene, octanal and capraldehyde were its major constituents (Hamdan et al, 2016;Martins et al, 2017). EOs from different Citrus species are chemically similar with the predominance of the monoterpene limonene, characteristics that are pointed out by Bozkurt et al (2017).…”
Section: Resultsmentioning
confidence: 71%
“…For example, at a concentration of 100 μg mL À 1 , the essential oil from Citrus limonia caused 100 % mortality of adult S. mansoni worms after 24 h (LC 50 = 38.9 μg mL À 1 ). [19] On the other hand, at a concentration of 50 μg mL À 1 , the EOs from C. limonia [19] and Piper marginatum [20] caused 100 % mortality of adult S. mansoni worms only after 72 h (LC 50 = 81.7 μm L À 1 for C. limonia at 24 h). Thus, comparison between the efficacies of different EOs must consider not only the concentration, but also the time needed for causing the adult worm death.…”
Section: Introductionmentioning
confidence: 99%